The manager as coach - Gilley, Jerry W.; Gilley, Ann Maycunich (Manager as--, 2007)
In theory, managers serve as guides, directors, decision makers, and energizers for their employees. Unfortunately, few managers have, themselves, been trained in the skills and techniques to get the best results from their employees, and managerial styles can run the gamut from permissive-but-ineffectual to aloof to autocratic. In The Manager as Coach, the authors focus on the key purposes of coaching-improving individual performance, solving problems, and securing results-in order to address the challenges of effective management head-on. Dispelling popular myths and misconceptions about coa.